2023
DOI: 10.3847/1538-4357/ace35b
|View full text |Cite
|
Sign up to set email alerts
|

The Crucial Role of Perpendicular Diffusion in the Longitude Distribution of >10 MeV Solar Energetic Protons

Yang Wang,
Gang Qin

Abstract: Gradual solar proton events are thought to consist of solar components originating near the Sun and interplanetary components associated with interplanetary shocks, and the role of interplanetary shocks is considered to be crucial in supplying particles to regions that are not magnetically connected to the solar source region. We calculate the ratios of the peak intensities for the four energy channels (13–16, 20–25, 32–40, and 40–64 MeV) and compare the ratios observed by multiple spacecraft at different loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The longitudinal difference between the source and the observer is different for different spacecraft and different events, so the observed intensities are different because of the perpendicular diffusion. Therefore, the number is different for STB and SOHO and also different for different events (Wang & Qin 2023). For the 13−16 MeV energy channel, STA observed only one peak in the 2010 August 14, 2011 November 3, and 2012 October 14 events, and the peak appeared approximately 3.62, 6.23, and 6.22 hr after the onset time of the SEPs, respectively.…”
Section: ( • • •mentioning
confidence: 96%
See 4 more Smart Citations
“…The longitudinal difference between the source and the observer is different for different spacecraft and different events, so the observed intensities are different because of the perpendicular diffusion. Therefore, the number is different for STB and SOHO and also different for different events (Wang & Qin 2023). For the 13−16 MeV energy channel, STA observed only one peak in the 2010 August 14, 2011 November 3, and 2012 October 14 events, and the peak appeared approximately 3.62, 6.23, and 6.22 hr after the onset time of the SEPs, respectively.…”
Section: ( • • •mentioning
confidence: 96%
“…In our recent work, we studied the peak intensities of singlepeak events observed by STEREO A (STA), STEREO B (STB), and the Solar and Heliospheric Observatory (SOHO) and calculated the peak ratios of four energy channels (13 −16 MeV, 20−25 MeV, 32−40 MeV, and 40−64 MeV;Wang & Qin 2023). We found that the peak ratios observed at different locations in the same SEP event were very similar.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations